Why projections on China's future food supply and demand differ - Fan, Shenggen; Agcaoili-Sombilla, Mercedita (Wiley, 1997)
This article analyses the macroeconomic assumptions, demand and supply parameters, and structures of the models used in projecting China's future food supply, demand and trade. Projections vary greatly, from China being self‐sufficient in grain to being a net importer of 369 million metric tons of grain in 2030. The differences stem mainly from the approaches chosen to model China's grain production and, in particular, the combined effects of land decline and yield growth. The article also points out improvements needed in future work on modelling China's grain economy, which include accounting for the links between agriculture and other sectors, technical change in the livestock industry and infrastructure constraints on grain imports.